Regulation of mitochondrial inner membrane fusion: divergent evolution with similar solutions? - Wagener, J. (Current Genetics, 2016)
Continuous mitochondrial fusion and fission define the dynamic shape of mitochondria. One essential player of mitochondrial fusion is the conserved inner membrane dynamin-like GTPase Mgm1/OPA1. Limited proteolysis of this protein has been proposed as a mechanism to separate and subsequently eliminate dysfunctional parts from the mitochondrial network. Here, I briefly summarize our current knowledge about the underlying proteolytic processing steps in mammals, baker's yeast, Schizosaccharomyces pombe, Drosophila melanogaster and Aspergillus fumigatus. The apparent great diversity in Mgm1/OPA1 processing among the analyzed species indicates a surprising mechanistic heterogeneity in the regulation of mitochondrial inner membrane fusion.